(3JaSjQ GdJMQjQs - (3GdMSf Hf eMeO Hf GdMSjf Gdbej GdfjSGHhQqi, fXGe GdOjf, hjbGd dg GdCYQL ` HYO (B850 (3g` s; (3GdfUjQ GdWhSj , eMeO Hf eMeO GdWhSj, fUjQ GdOjf CHh LYaQ,J (B672 (3g` s ((3eOjfI JHQjR s)
(3ChdgG (B:s
(3GdSYO bQjf ef UOQ cdGeg HGdMeO dhGgH GdSYGOI hHYO , aef GdeYdhe Cf cJGH GdeLSWi GdefShH Edi HWdjehS GdbdhPi cJGH TgO dg GdYGdehf ai ENJQGYg HGdbOM GdeYdi s
(3BNQgG (B:s
(3hdSJ CdJeS HgPG GdOYGA EKHGJ gPg GdCTjGA dhRjQ GdhRQGA aGdJeGS Pdc jchf JMUjdkG ddMGUd Hd GdedJeS efg JYGdi Gf jfYe Ydjg dMXI HdMXI s
(3HgG fXGe GdJYbjHIs
(3HgG QShe hCTcGd gfOSjIs
(3aQZ GdeDda ef JaSjQg SfI (B704(3g`s
(3cJHJ Hbde eged GdfbW bdjdkG s
(3HBNQgG HNW GdeDda Cfg UMMgG Yf BNQgG HChdgG dhMI ePgHI HQSe NRGfI bWH GdOjf GdTjQGRi s
(3bQf GdfSN (B:s
Keywords: (3Gdadcs